Electricity Pricing in New Zealand and the Australian State of Queensland: Accounting for the Impact of Sector Restructuring. (16th September 2015) - Hooks, Jill; Tooley, Stuart
Abstract: The electricity industries of New Zealand (NZ) and the Australian state of Queensland have undergone substantial structural and regulatory reform with the common intent to improve economic efficiency. Deregulation and privatisation have been key elements of the reform but have been approached differently by each jurisdiction. This study traces the link between structural and regulatory regimes and asset valuation, profits and, ultimately, pricing. The study finds that key drivers in recent price increases are the government‐owned generation and retail sector in NZ and the government‐owned distribution sector in Queensland. It is concluded that, contrary to the rationale for the imposition of regulatory controls in a non‐market environment, the regulatory regimes appear to have contributed to higher rather than lower pricing structures.